LUMINESCENCE SPECTROSCOPY OF NATURAL AND SYNTHETIC REE-BEARING MINERALS - Friis H. (My University, 2009)
This study investigates the photoluminescence (PL), cathodoluminescence (CL), radioluminescence (RL) and ionoluminescence (IL) of natural and synthetic minerals. The natural minerals (fluorapatite, leucophanite, meliphanite and zircon) are mostly from Ilímaussaq Alkaline Complex in South Greenland, Langesundsfjord in Norway and from different localities within Scotland. Synthetic fluorapatite (manufactured as part of the present study) and zircon doped with rare earth elements (REE) were used to compare single and multidoped materials.
Keywords: luminescence; REE